9th South Asian Management Forum : management for peace, prosperity, and posterity, 24-25 February 2007 : proceedings - South Asian Management Forum 2007 : Dhaka, Bangladesh); Association of Management Development Institutions in South Asia.; North South University; South Asian Association for Regional Cooperation (Dhaka : Published by AMDISA and North South University, 2007)
Transcript of papers chiefly on industrial management in South Asia.
At head of title: Association of Management Development Institutions in South Asia.
"Hosted by North South University, Dhaka, Bangladesh, South Asian Association for Regional Cooperation."
Includes statistics.
Includes bibliographical references.
Keywords: Industrial management -- South Asia -- Congresses; Industrial management -- South Asia -- Statistics -- Congresses